2015
DOI: 10.1097/hp.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Simple and Efficient Monthly Quality Management Program Assessing the Consistency of Robotic Image-Guided Small Animal Radiation Systems

Abstract: Modern pre-clinical radiation therapy (RT) research requires high precision and accurate dosimetry to facilitate the translation of research findings into clinical practice. Several systems are available that provide precise delivery and on-board imaging capabilities, highlighting the need for a quality management program (QMP) to ensure consistent and accurate radiation dose delivery. An ongoing, simple, and efficient QMP for image-guided robotic small animal irradiators used in pre-clinical RT research is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…We found that the maximum beam‐targeting displacement for the delivery isocenter (laser intersection) was 1.95 ± 0.04 mm before our SARRP mechanical calibration, which dropped to 0.76 ± 0.09 mm after calibration. This value is consistent with Brodin's value for target localization accuracy of SARRP …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that the maximum beam‐targeting displacement for the delivery isocenter (laser intersection) was 1.95 ± 0.04 mm before our SARRP mechanical calibration, which dropped to 0.76 ± 0.09 mm after calibration. This value is consistent with Brodin's value for target localization accuracy of SARRP …”
Section: Discussionsupporting
confidence: 91%
“…In previous works, Brodin et al. had suggested a methodology to measure the beam‐targeting alignment of the SARRP system . Because of difficulty in acquiring good quality portal images at different gantry angles, Brodin et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple examples exist in the literature of QA regimens for initial commissioning and routine maintenance. [45][46][47] Key elements are QA testing for dose rate constancy, imaging quality and targeting localizations that are performed on a regular basis. More advanced dosimetry techniques for small animal research may be based on using an imaging panel, in analogy with portal dosimetry in RT.…”
Section: Advances In Small Animal Irradiationmentioning
confidence: 99%